2015
DOI: 10.1016/j.dcn.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Neural substrates of child irritability in typically developing and psychiatric populations

Abstract: Irritability is an aspect of the negative affectivity domain of temperament, but in severe and dysregulated forms is a symptom of a range of psychopathologies. Better understanding of the neural underpinnings of irritability, outside the context of specific disorders, can help to understand normative variation but also characterize its clinical salience in psychopathology diagnosis. This study assessed brain activation during reward and frustration, domains of behavioral deficits in childhood irritability. Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
121
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 58 publications
7
121
0
Order By: Relevance
“…Although previous investigations into the neural underpinnings of temperament, both in the anxious [Fox et al, ; Guyer et al, ; Perez‐Edgar et al, ; Perlman and Pelphrey, ; Schwartz et al, ] and irritable [Deveney et al, ; Grabell et al, ; Perlman et al, , ] domains demonstrate distinct patterns of activation during negative emotion, our study only found this effect when examining the irritable domain. We propose two possible reasons for this unique finding.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous investigations into the neural underpinnings of temperament, both in the anxious [Fox et al, ; Guyer et al, ; Perez‐Edgar et al, ; Perlman and Pelphrey, ; Schwartz et al, ] and irritable [Deveney et al, ; Grabell et al, ; Perlman et al, , ] domains demonstrate distinct patterns of activation during negative emotion, our study only found this effect when examining the irritable domain. We propose two possible reasons for this unique finding.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a study using functional near infrared spectroscopy imaging in a sample of preschool children, decreased lateral PFC activity was associated with increased frustration tolerance [76]. In older youth, studies of frustration during fMRI or magnetoencephalography show associations between irritability and ACC, striatal, medial PFC, parietal and amygdala activity [7375, 77] (Figure 3). Somewhat unexpectedly, in two fMRI studies irritability is associated with decreased amygdala activation during frustration [74,75].…”
Section: Reward Processing In Irritable Youthmentioning
confidence: 99%
“…For example, compared to healthy controls, young children (ages 6- 9) with clinically significant symptoms of irritability exhibit decreased activation of the ACC in response to frustration (Perlman et al, 2015). This contrasts an earlier magnetoencephalography (MEG) study with a similar, yet older sample of children (ages 8- 17) with SMD, who showed greater activation of ACC, along with higher ratings of agitation and sadness, in response to negative feedback, as compared to healthy controls (Rich et al, 2011).…”
Section: Frustration Reward and Non-rewardmentioning
confidence: 99%